Digital library use : - Bishop, Ann Peterson (MIT Press, 2003)
Introduction : digital libraries as sociotechnical systems / Nancy A. Van House, Ann Peterson Bishop, and Barbara P. Buttenfield -- Documents and libraries : a sociotechnical perspective / David M. Levy -- Finding the boundaries of the library without walls / Catherine C. Marshall -- Ecological perspective on digital libraries / Vicki L. O'Day and Bonnie A. Nardi -- Designing digital libraries for usability / Christine L. Borgman -- People in digital libraries : multifaceted approaches to assessing needs and impact / Gary Marchionini, Catherine Plaisant, and Anita Komlodi -- Participatory action research and digital libraries : reframing evaluation / Ann Peterson Bishop ... [et al.] -- Colliding with the real world : heresies and unexplored questions about audience, economics, and control of digital libraries / Clifford Lynch -- Information and institutional change : the case of digital libraries / Philip E. Agre.